Effect of processing parameters on microstructure during laser-sustained plasma (LSP) nitriding of commercially-pure titanium. (1st April 2016) - Kamat, Amar M.; Copley, Stephen M.; Todd, Judith A.
Abstract: A nitrogen plasma can be sustained in air using a high-power CO2 laser. If nitriding of a Ti substrate is performed in the presence of such laser-sustained plasma (LSP) in open atmosphere, the following effects have been previously reported: increase in nitrogen intake, wider surface coverage, reduction in surface oxidation, and no attenuation of energy transfer to the substrate. This investigation expands on previous work by systematically studying the effects of varying process parameters on microstructure during LSP nitriding of CP-titanium. Microstructural features are reported as a function of off-focal distance, scan speed of the laser, and nitrogen:argon gas flow ratio. The top surfaces and transverse cross sections of these single trail nitriding runs were observed using optical and scanning electron microscopy. X-ray diffraction (XRD) and optical profilometry techniques were used to characterize the nitrided surface layer. The presence of LSP increased the solubility of nitrogen in liquid titanium leading to gas recombination and expulsion on the surface. This tendency decreased with increasing speed. Nitrogen dilution by argon was found to reduce crack formation. Further, nitrogen dilution reduced Marangoni convection in the melt pool. This changed the nitrogen transport mechanism in the melt pool from convection-dominated to diffusion-dominated, thus reducing nitrogen incorporation into the melt pool. Argon addition was also found to reduce surface roughness and surface oxidation. XRD and scanning electron microscopy revealed the presence of phases such as TiN, TiN0.3 and acicular martensitic titanium (α′-Ti). Future work will focus on depositing multiple overlapping nitride trails to form wide-area titanium nitride surface layers. Graphical abstract: